A meta-analytic review of cognitive processing therapy for adults with posttraumatic stress disorder. Issue 1 (2nd January 2019) - Asmundson, Gordon J. G.; Thorisdottir, Audur S.; Roden-Foreman, Jacob W.; Baird, Scarlett O.; Witcraft, Sara M.; Stein, Aliza T.; Smits, Jasper A. J.; Powers, Mark B
ABSTRACT: Numerous studies have demonstrated the efficacy of cognitive processing therapy (CPT) for treating posttraumatic stress disorder (PTSD). Two prior meta-analyses of studies are available but used approaches that limit conclusions that can be drawn regarding the impact of CPT on PTSD outcomes. The current meta-analysis reviewed outcomes of trials that tested the efficacy of CPT for PTSD in adults and evaluated potential moderators of outcomes. All published trials comparing CPT against an inactive control condition (i.e. psychological placebo or wait-list) or other active treatment for PTSD in adults were included, resulting in 11 studies with a total of 1130 participants. CPT outperformed inactive control conditions on PTSD outcome measures at posttreatment (mean Hedges' g  = 1.24) and follow-up (mean Hedges' g  = 0.90). The average CPT-treated participant fared better than 89% of those in inactive control conditions at posttreatment and 82% at follow-up. Results also showed that CPT outperformed inactive control conditions on non-PTSD outcome measures at posttreatment and follow-up and that CPT outperformed other active treatments at posttreatment but not at follow-up. Effect sizes of CPT on PTSD symptoms were not significantly moderated by participant age, number of treatment sessions, total sample size, length of follow-up, or group versus individual treatment; but, older studies had larger effect sizes and percent female sex moderated the effect of CPT on non-PTSD outcomes. These meta-analytic findings indicate that CPT is an effective PTSD treatment with lasting benefits across a range of outcomes.